Persepsi Guru Terhadap Gaya Kepemimpinan Kepala Sekolah di SDN Ngabeyan 3 Kartasura - Alfian, Muhammad Bahar; , Drs. Suwarno, SH,M.Pd (2017)
This research aims to (1) describe the perceptions of teachers toward the leadership style in elementary school principal N Ngabeyan 3 Kartasura, (2) know the principal leadership style in SD N Ngabeyan 3's debt. This research is a descriptive qualitative research. Data analysis includes the reduction of the data, the presentation of the data and the withdrawal of the conclusion. Techniques of examination ofthe validity of the data by using triangulation. The results of this research indicate(1) the teacher's Perception towards the principal leadership style between teachersand other teachers, school principal be nice already but still have sikpa favoritism and less close to young teachers. (2) the principal leadership style which are used in lead is a democratic style school where the headteacher is always strives for a sense of unity and togetherness and unity in the face of anything. The solution is the head of the school should not have the attitude of sort-choose to avoid a sense of envy among young and senior teachers and between teachers young and seniors should be more berkordinasi with better again. Keywords: perception, teacher, leadership style, principal